U.S. Production Trends and the Impact of the Florida Fresh Market Tomato Industry to the Economy of Florida - John J. VanSickle; Alan W. Hodges (EDIS)
FE749, a 6-page fact sheet by John J. VanSickle and Alan W. Hodges, describes trends in tomato production and provides estimates for the total regional impacts of the Florida tomato industry using IMPLAN input output modeling system. Includes references. Published by the UF Department of Food and Resource Economics, September 2008.